PERAN GURU DALAM PENGENALAN LITERASI DIGITAL PADA ANAK USIA DINI PADA MASA COVID-19 DI TK SE-KECAMATAN PAUH DUO - Agung Prayoga; Elise MUryanti (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
This study was conducted to see the extent to which the role of teachers in the introduction of early childhood digital literacy during the COVID-19 pandemic in kindergartens throughout Pauh Duo District, South Solok Regency. This study resulted that the overall average role of teachers in the introduction of digital literacy in early childhood during the Covid-19 pandemic in kindergartens in the Pauh Duo District, Solok - South Regency showed a figure of 57.42% in the less category with a score of <62 .5%, that is, it can be said that the role of teachers in the introduction of digital literacy in early childhood is in the less category, and it is necessary to increase the digital literacy competence of teachers in kindergartens in Pauh Duo Sub-district, Solok Regency - South.